Submucosal Tunnel Endoscopic Resection for Esophageal Submucosal Tumors: A Multicenter Study - Sufang Tu; Silin Huang; Guohua Li; Xiaowei Tang; Haitao Qing; Qiaoping Gao; Jingwen Fu; Guoping Du; Wei Gong (Gastroenterology Research and Practice)
Background. Submucosal tumors (SMTs) are primarily benign tumors, but some may have a malignant potential. Endoscopic submucosal dissection that has been used for removing esophageal SMTs could cause perforation. Submucosal tunnel endoscopic resection (STER) is an improved and an effective technique for treating esophageal SMTs. Aims. This study was conducted to evaluate the efficacy and safety of STER for treating esophageal SMTs. Methods. A retrospective study design was adopted to analyze the baseline characteristics, clinical outcomes, and follow-up data of patients with esophageal SMTs, which originated from the muscularis propria layer and were treated with STER from September 2011 to May 2018. Results. A total of 119 lesions were included from 115 patients who were successfully treated with STER. The mean age of the patients was 49.7 ± 10.7 years. The lesions were primarily located in the middle and lower esophagus. The mean size of the lesions was 19.4 ± 10.0 mm. The mean operation duration was 46.7 ± 25.6 min, and the mean duration of hospitalization was 5.9 ± 2.8 days. The total en bloc resection rate and the complete resection rate were 97.5% and 100%, respectively. Regarding complications, there were 9 (7.8%) cases of perforation, 2 (1.7%) cases of pneumothorax, and 9 (7.8%) cases of subcutaneous emphysema. Histopathological results revealed 113 (95.0%) cases of leiomyoma, 5 (4.2%) cases of gastrointestinal stromal tumors, and 1 (0.8%) case of a granular cell tumor. During the mean 15-month follow-up, there were no cases of recurrence and distant metastasis. Conclusions. STER is a safe and feasible technique for treating esophageal SMTs originating from the muscularis propria layer.